Deep-Seated Deformation Mechanisms of Excavated Slope and Control Methods: A Case Study - Wu, Yongjin; Zhang, Qing; Ding, Xiuli; Wang, Hui; Huang, Shuling; Yin, Xiansong (Frontiers in Earth Science, 2022)
High slope stability control is a crucial technical issue in water conservancy and hydropower project construction. This issue is relevant throughout the entire engineering-related survey, design, construction, and operation process. This paper reports a recent case in which significant deep-seated deformation occurred during slope excavation. Several unfavorable structural surfaces were revealed throughout the slope’s undercutting process, particularly fault fz39, which ran diagonally through the entire slope from top to bottom. On the slope surface, damage such as cracking, bulging, and local slippage appeared. The measured value of multipoint displacement meters increased in a stepwise pattern with each blast, and the maximum measured value exceeded 100 mm. The studied slope’s whole excavation and reinforcement process is described in detail. We analyzed the deformation mechanism of the excavation slope by combining the geological conditions, real-time safety monitoring findings, and site deformation characteristics. The slope reinforcement scheme was optimized based on the preceding analyses. We used a three-dimensional numerical calculation program to simulate the slope excavation and unloading process to reproduce the current mechanical state of the slope, evaluate the reinforcement measures, and provide a useful reference for decision making. The analysis shows that the deformation behavior of the studied slope is closely related to fault fz39 and fracture L920, and presents a typical wedge failure mode. The deep-seated deformation of the excavation slope occurs at the junction of the wedge and bedrock, which is mainly affected by unfavorable geological structure surfaces, excavation unloading, and blasting vibration. The reinforcement scheme of unloading at the top of the slope and large-tonnage cables are established. The numerical analysis results showed that the design of the slope reinforcement measures was appropriate and ensured slope stability. The work described in this paper deepens our understanding of the occurrence of large deep-seated deformation on the structural-controlled slope under the action of excavation and improves the design philosophy.